1990
DOI: 10.5935/0305-7518.19900025
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical distribution of single leprosy lesions in an African population, and its implications for the pathogenesis of leprosy

Abstract: Data on the anatomical sites of single leprosy lesions found in 635 newly diagnosed and biopsy-confirmed leprosy patients are presented. These patients were found during total population surveys carried out by the Lepra Evaluation Project, a prospective longitudinal study of the epidemiology of leprosy in Karonga District, Northern Malawi. There was a striking excess of single lesions on the face and the back of the arms, compared to the distribution of skin surface area, and a deficit on the legs, regardless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…Mycobacterium leprae has also been observed in the epidermis and in epidermal washings of multibacillary leprosy cases 6,10–12 . The first leprosy lesion, probably the point of the organism's entry, commonly occurs on exposed trauma‐prone body parts 13 …”
mentioning
confidence: 99%
“…Mycobacterium leprae has also been observed in the epidermis and in epidermal washings of multibacillary leprosy cases 6,10–12 . The first leprosy lesion, probably the point of the organism's entry, commonly occurs on exposed trauma‐prone body parts 13 …”
mentioning
confidence: 99%
“…In Palmas, incidence rates for males and females did not show important differences 3 . Ponnighaus et al 33 showed that skin lesions in females are more frequently found on the face and arms as compared to males. These differences in lesion location facilitate the identification of early leprosy in women.…”
Section: Discussionmentioning
confidence: 99%
“…Percentages refer to the proportion of all single lesions, in males and females separately, and the proportion of total body surface area, on each anatomical site. 53 a detailed clinical description of the lesion from which a biopsy was taken, including results of sensory testing. This resulted in a policy shift in late 1985 so that the histopathologist was thereafter told only the location on the body from which the biopsy was obtained.…”
Section: Leprosy Presentation and Diagnosismentioning
confidence: 99%